2020
DOI: 10.1017/s1755691020000079
|View full text |Cite
|
Sign up to set email alerts
|

A review of the stem amnioteEldeceeon rolfeifrom the Viséan of East Kirkton, Scotland

Abstract: The late Viséan anthracosauroid Eldeceeon rolfei from the East Kirkton Limestone of Scotland is re-described. Information from two originally described and two newly identified specimens broadens our knowledge of this tetrapod. A detailed account of individual skull bones and a revision of key axial and appendicular features are provided, alongside the first complete reconstructions of the skull and lower jaw and a revised reconstruction of the postcranial skeleton. In comparison to Silvanerpeton, the only oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“… Anderson et al (2015) reported a number of isolated anthracosaur [PN] (embolomere or eoherpetid) bones from a mid-Tournaisian site (the Tournaisian preceded the Viséan and began at the Devonian/Carboniferous boundary 358.9 ± 0.4 Ma ago: ICSC). Whether these are tetrapods depends on the relative positions of temnospondyls, anthracosaurs and other clades in that region of the tree ( Pardo et al, 2018 , 2020 ; Marjanović and Laurin, 2019 ; Ruta et al, 2020 ; and references in all four) in addition to the position of Lissamphibia: even if the lissamphibians are temnospondyls, the anthracosaurs may still be stem-stegocephalians.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“… Anderson et al (2015) reported a number of isolated anthracosaur [PN] (embolomere or eoherpetid) bones from a mid-Tournaisian site (the Tournaisian preceded the Viséan and began at the Devonian/Carboniferous boundary 358.9 ± 0.4 Ma ago: ICSC). Whether these are tetrapods depends on the relative positions of temnospondyls, anthracosaurs and other clades in that region of the tree ( Pardo et al, 2018 , 2020 ; Marjanović and Laurin, 2019 ; Ruta et al, 2020 ; and references in all four) in addition to the position of Lissamphibia: even if the lissamphibians are temnospondyls, the anthracosaurs may still be stem-stegocephalians.…”
Section: Methodsmentioning
confidence: 99%
“…Colosteidae (“Colosteida” of Pardo et al, 2020 ) was referred to Temnospondyli throughout the 20th century and found in that position by Marjanović and Laurin (2019) to our great surprise (also in some of the trees by Daza et al, 2020 : supplementary figure S15); as pointed out by Pardo et al (2020) , this means it could belong to Tetrapoda. However, ongoing work on enlarging and improving the matrix of Marjanović and Laurin (2019) and Daza et al (2020) shows that this result was most likely an artifact of the taxon and character sample; similarly, Ruta et al (2020) found the colosteid they included to be a temnospondyl with weak support in their Bayesian analysis, but to lie rootward of Temnospondyli in their parsimony analyses (unweighted, reweighted, or with implied weighting).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…S15); as pointed out by Pardo et al (2020), this means it could belong This is a provisional file, not the final typeset article to Tetrapoda. However, ongoing work on enlarging and improving the matrix of Marjanović and Laurin (2019) and Daza et al (2020) shows this result was most likely an artefact of the taxon and character sample; similarly, Ruta et al (2020) found the colosteid they included to be a temnospondyl with weak support in their Bayesian analysis, but to lie rootward of Temnospondyli in their parsimony analyses (unweighted, reweighted or with implied weighting).…”
Section: Node 105: Tetrapoda [Pn] (Amphibia [Pn] -Pan-amniota [Pn])mentioning
confidence: 98%
“…This level of diversity among tetrapods is not encountered again until the mid-Pennsylvanian, some 25 million years (Myr) later, by which time several clades, particularly among crown Amniota, are well established and greatly diversified 1 . Among the tetrapods represented at East Kirkton are the temnospondyl Balanerpeton 2 , the anthracosaur-like Silvanerpeton 3 , 4 and Eldeceeon 5 , 6 , and the amniote-like Westlothiana 7 . In some recent studies 8 10 , these taxa have been placed phylogenetically as the earliest known members of stem Amphibia ( Balanerpeton ) or stem Amniota ( Westlothiana ; Silvanerpeton ; Eldeceeon ; but see ref.…”
Section: Introductionmentioning
confidence: 99%